Analysis of Using Google Maps Data to Measure the Presence or Accessibility of Urban Facilities for BPS - Statistics Indonesia Classification of Urban and Rural Villages - Benny Firmansyah; Widya Sri Wahyuni (Journal of Information System and Informatics, 2022)
The BPS - Statistics Indonesia classifies villages into urban villages and rural villages to organize statistics. The classification of village areas into urban or rural status is intended to form a stratum used in survey sampling techniques. With this status, it is hoped that the sample taken can represent the entire population well. The BPS - Statistics Indonesia establishes criteria for classifying a village into an urban village. The 2020 urban village criteria use three indicators as its measure, namely: population density per km2, percentage of agricultural families, and the presence or access of urban facilities. In general, the data used in calculating the classification of urban and rural villages in 2020 uses data from the 2019 Village Potential (Podes) survey. This study utilizes data on urban facilities such as schools, markets, shops, and hospitals on the google maps website to calculate the score of indicators of the existence or access of urban facilities. This study used a web scraping method to obtain data on these urban facilities from the google maps website. This study selected eight villages in the Lubuk Sikaping District, Pasaman Regency, West Sumatra Province, as a case study. The results showed that four villages with great potential were classified into urban villages, and three villages with great potential were classified into rural villages.